EXPERIENCE OF THE SUCCESSFUL CANAKINUMAB TREATMENT OF A PATIENT WITH UNDIFFERENTIATED AUTOINFLAMMATORY SYNDROME - Tatyana V. Sleptsova; Еkaterina I. Alexeeva; Тatyana М. Bzarova; Kirill V. Savostyanov; Аlexander A. Pushkov; Kseniya B. Isaeva; Rina V. Denisova; Оlga L. Lomakina (Вопросы современной педиатрии, 2016)
The article presents a case of a successful canakinumab application (preparation of monoclonal antibodies to 1 interleukin) for undifferentiated autoinflammatory syndrome in a patient with refractoriness to oral glucocorticosteroids and genetically engineered biological drugs with a different action mechanisms. After 8 weeks of canakinumab therapy, systemic manifestations were cropped, and laboratory parameters of the disease activity were normalized. During the entire care period (12 months), neither serious adverse events nor increased incidence of acute respiratory infections have been reported.